KAJIAN BIBLIKAL SPIRITUALITAS HAMBA TUHAN BERDASARKAN 2 TIMOTIUS 2:1-13 - Minggus Dilla (Manna Rafflesia, 2016)
Spirituality is an integral part of human life. Spirituality influences the attitude of the heart and human thought patterns. Many problems occur in human life and it starts from the problem of spirituality. Thus learning about spirituality is needed. There are many methods offered by religions in the world to form spirituality. In the Christian faith the Bible is the basis for building spirituality. In Paul's Letter to Timothy gives important teachings about spirituality. Therefore, to provide insight into spirituality, this article will write about the Biblical Study of the spirituality of God's servants based on 2 Timothy 2: 1-13.